Vesicle Trafficking in Cancer - Yarden, Yosef; Tarcic, Gabi (Springer New York : Imprint: Springer, 2013)
Endocytosis and vesicular trafficking determine the landscape of the cell's exterior, namely the density of surface molecules, such as receptors for growth factors and cytokines, adhesion molecules like integrins and cadherins, and a plethora of nutrient carriers. Hence, endocytosis is involved in signal transduction, cell adhesion and migration, as well as metabolism. To exploit these fundamental processes, malignancies subtly and multiply manipulate the endocytosis and the subsequent trafficking of protein cargoes. This is achieved by simultaneously altering the cytoskeleton, vesicle budding, cargo sorting and intracellular degradation. By highlighting the underlying molecular processes and concentrating on specific examples, this book reviews the recent emergence of derailed endocytosis and vesicular trafficking as a landmark of cancer. In-depth understanding of this common feature of tumors might lead the way to drug-induced strategies, able to rectify intracellular trafficking in cancer.